Improvement in the Methodological Estimation of Sulfur Hexafluoride Use in Electrical Equipment for Malaysias National Greenhouse Gas Inventory - Tan E.S.; Pua F.L.; Verayiah R.; Syazalina N. (Multidisciplinary Digital Publishing Institute (MDPI), 2024)
Sulfur hexafluoride (SF6) gas is one of the high global warming potential (GWP) gases regulated under the Kyoto Protocol. In Malaysias Biennial Update Report 3, the Revised 1996 Intergovernmental Panel on Climate Change Guidelines were followed to estimate the SF6 emissions in the country, including the time series from 1990 to 2016. The majority of SF6 emissions originate from the use of this gas in electrical equipment, where it is predominantly used in transmission switch gears, which have increased rapidly because of increasing electricity demand. SF6 gas plays a significant role in greenhouse gas emissions in Malaysia because this gas has a higher GWP than carbon dioxide. Hence, this SF6 gas needs to be estimated using newer guidelines such as the 2006 IPCC Guidelines. Detailed activity data in the new methodology require stakeholders engagement with utility providers and government agencies. This paper describes the GHG inventory improvement plan, focusing on SF6 emissions for Industrial Processes and Product Use for Malaysia through this transition of methodology. 2023 by the authors.